Chiral nematic liquid crystal droplets as a basis for sensor systems. Issue 6 (16th March 2022) - Paterson, Daniel A.; Du, Xiaoxue; Bao, Peng; Parry, Adele A.; Peyman, Sally A.; Sandoe, Jonathan A. T.; Evans, Stephen D.; Luo, Dan; Bushby, Richard J.; Jones, J. Cliff; Gleeson, Helen F.
Abstract : For a series of phospholipid coated calamitic nematic liquid crystal droplets the addition of chiral dopant leaves the sign of surface anchoring unchanged but changes the director structure from Frank–Pryce to nested-cup inducing a strong optical change suitable for sensing. Abstract : For a series of phospholipid coated calamitic nematic liquid crystal droplets (5CB, 6CB, 7CB, E7 and MLC7023) of diameter ∼18 μm, the addition of chiral dopant leaves the sign of surface anchoring unchanged. Herein we report that for these chiral nematic droplets an analyte induced transition from a Frank–Pryce structure (with planar anchoring) to a nested-cup structure (with perpendicular anchoring) is accompanied by changes in the intensity of reflected light. We propose this system as both a general scheme for understanding director fields in chiral nematic liquid crystal droplets with perpendicular anchoring and as an ideal candidate to be utilised as the basis for developing cheap, single use LC-based sensor devices.